Single Nuclear Polymorphisms of VEGF, TGF-β1, MMP9 Genes in Type 2 Diabetic Foot Ulcer Patients in Indonesian Population: A Case Control Study - Dedy Pratama (Journal of Global Pharma Technology, 2020)
Objective: Vascular endothelial growth factor (VEGF), transforming growth factor beta 1 (TGF-β1) and matrix metalloprotein-9 (MMP9) are known to have roles in the process of diabetic foot ulcer (DFU) formation. VEGF rs2010963C>G rs1271283232T>C, TGF-β1 rs1982073C>T rs1800469C>T, and MMP9 rs3918242C>T rs367601348A>G genes polymorphism may result in differences in the quantity and quality of the proteins which influence the risk of DFU formation. This study aims to assess the difference in frequency distribution of certain VEGF, TGF-β1, and MMP9 genes polymorphism between diabetic patients with and without DFU.Methods: A case-control study was conducted among patients with type-2 DM with DFU (case) and without DFU (control) in Cipto Mangunkusumo Hospital Jakarta, with DNA analysis using Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) technique. The confounding factors are also analyzed.Results: A total of 197 patients was assessed, 96 with DFU and 101 control. The genotype analysis by logistic regression found significant association of CT genotype in TGF-β1 rs1982073C>T  (OR:0.28;95%CI:0.13-0.60;p=0.001 compared with CC); TT genotype in TGF-β1 rs1800469C>T, (OR:2.37;95%CI:1.11-0.60;p=0.001 compared with CC); TC genotype in MMP9 rs3918242C>T (OR:0.19;95%CI:0.19-0.64;p=0.001 compared with CC). There are no significant association in any mutation in VEGF rs2010963C>G, rs1271283232T>C, and MMP9 rs367601348A>G.Conclusion: VEGF rs2010963C>G rs1271283232T>C, and MMP9 rs367601348A>G polymorphisms did not have significant association with DFU formation. CT in TGF-β1 rs1982073C>T and TC in MMP9 rs3918242C>T found as protective factor for DFU, and TT in TGF-β1 rs1800469C>T as risk factor for DFU.Keywords: diabetic foot ulcer, genetic polymorphism, VEGF, MMP9, TGF-β1, rs2010963C>G, rs1271283232T>C, rs1982073C>T, rs1800469C>T, rs3918242C>T rs367601348A>G